Kilovolt Variation and Digital Image Contrast: Phantom Study Comparison - Yudha, Sagita; Dewilza, Nerifa; Sari, Oktavia Puspita; Nisa, Chairun; Vania, V (Department of Physics – Universitas Negeri Padang UNP, 2025)
An exposure factor that is too high can result in radiography results that are too black (dark), and an exposure factor that is too low can result in results that are white (bright). Providing an inappropriate exposure factor can prevent the radiograph from providing the best information. When the exposure factor is set properly, radiographic contrast can be maximized, allowing different organs with varying densities to be clearly distinguished from one another in terms of blackness. This kind of research combines an experimental study with quantitative methods. The experimental approach can be understood as a research technique to compare treatments with one another in a controlled environment in order to compare kV fluctuations in the pelvic phantom and achieve the best possible picture quality (contrast). The data processed in the Image J application in the form of a histogram graph is strengthened by data processing using SPSS and the Friedman test. Based on the results of the analysis of the Friedman test, there is an influence, the results obtained at kV 70 show the highest mean rank of 4.57 and in the image J application it shows at kV 70 with graphic results on the histogram of contrast levels which are good, then the radiographic results of the comparison of variations in kV versus contrast in the optimal pelvic phantom are obtained, namely at kV 70.